El contagio en el fracaso empresarial como consecuencia de la proximidad geográfica: Un análisis con los estadísticos join-count aplicado al sector servicios - Christian Camilo Rodríguez Fuentes; María Luz Maté Sánchez-Val; Fernando A. López Hernández (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
– This paper aims to contrast the spillover effects in business failure derived from the geographic proximity among firms of the same sector. To get this purpose, we develop an empirical application based on the analysis of the join-count statistics on a sample of firms of service sector located in the municipality of Murcia (Spain). Our results show significant spatial autocorrelation pattern, therefore, the probability of failure in a firm not only depends on its internal characteristics, but also on the situation of failure of its vicinity peer companies. These results can be an interesting starting point in the development of papers which consider the interdependence effects among closer peer companies in business failure literature.
Keywords: C49; L80; R39; 330; Spatial autocorrelation; business failure; join-count test